Mandok Hata pada Malam Tahun Baru: Merenungkan Makna Pengampunan dalam Budaya Batak dan Ajaran Kristen : Kolose 3:13 (Jurnal Pendidikan Agama dan Teologi, 2024)
In the article titled "Mandok Hata on New Year's Eve: Reflecting on the Meaning of Forgiveness in Batak Culture and Christian Teachings (Colossians 3:13)", the author uses a qualitative approach through the analysis of literature related to Mandok Hata and forgiveness. The Mandok Hata ritual on New Year’s Eve reflects spiritual and social values, where the Batak Toba community apologizes to each other, strengthens family ties, and creates an atmosphere of reconciliation. The author asserts that forgiveness in Christian teaching, as an unconditional gift of God, is internalized in this practice. This article shows that forgiveness and Mandok Hata are complementary, encouraging social and spiritual harmony, as well as starting the new year with a clean and loving heart.